Perkembangan Peradaban Arab: Jejak Sejarah dan Tantangan di Era Globalisasi - Perenia, Fityani; Hasaniyah, Nur (CV. Kurnia Grup, 2025)
This article explores the development of Arab civilization with a focus on historical traces and challenges faced in the era of globalization. Through historical and sociological studies, this research traces the contribution of the Arab people to science, philosophy and art, which reached its peak during the Abbasid era. The cultural and social transformations that occurred after the era of colonialism are also reviewed, including how Arabs adapted to modernity while maintaining their cultural identity. Globalization has had a significant impact on contemporary Arab civilization, especially in terms of the influence of technology, media and global mobility. The main challenges faced are maintaining traditional values amidst rapid changes and redefining cultural identity in the Arab diaspora. With a qualitative approach based on literature review and document analysis, this research highlights the efforts of Arab society in preserving cultural heritage while aligning didi with the demands of the digital era. This article concludes that, despite facing various challenges, Arab civilization has great potential to continue to contribute to the global realm, provided a strong cultural identity is maintained. It is hoped that these findings will provide insight into the dynamics of Arab civilization and its relevance for civilization studies in the modern era.